Inhalable nanoparticle-based delivery systems for the treatment of pulmonary infections: Status quo and barrier-overcoming strategies - Yihong Gao; Wenhao Wang; Xiao Yue; Guanlin Wang; Kaiqing Zhang; Chuanbin Wu; Ziyu Zhao; Zhengwei Huang; Xuejuan Zhang (Drug Delivery)
Pulmonary infection is a serious public health challenge with high morbidity and mortality. The employment of antibiotics is the first-line treatment for pulmonary infections, while other novel anti-infection agents, such as antimicrobial peptides, have also been developed due to the emergence of drug resistance. Recently, inhalable nanoparticle-based delivery systems have garnered significant attention for the delivery of anti-infection agents, which possess great advantages like high lung accumulations and precise delivery performances. However, the respiratory physiological structure, mucus and biofilm have been considered as the barriers that nanoparticle drug delivery systems facing, which compromise the therapeutic effects. In this integrative review, recent advances in the inhalable nanoparticle-based delivery system were introduced. In addition, we focused on the biological characteristics of these barriers and discussed effective strategies to overcome the obstacles, including precise deposition in the lower respiratory tract infection site, effective penetration of mucus and breaking of the biofilm barrier. To sum up, this review aimed to deepen the understanding of the fate of anti-infective nanoformulations in pulmonary delivery and find effective strategies to address the barriers, thus providing new insights for the development of pulmonary delivery systems against pulmonary infections.